Klasifikasi online dan google - Irma Devi Lestari (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2016)
The purpose of this paper is to examine challenges facing bibliographic classification at both the practical and theoretical levels. At the practical level, libraries are increasingly dispensing with classifying books. At the theoretical level, many researchers, managers, and users believe that the activity of “classification” is not worth the effort, as search engines can be improved without the heavy cost of providing metadata.